Fatal tumor lysis syndrome in a patient with metastatic gastric adenocarcinoma - Robin Moiseff; Cameron Felty; Xiaoying Liu (University of São Paulo, 2021)
Tumor lysis syndrome is a well-characterized and potentially deadly complication of spontaneous or treatment-related tumor destruction, and it is most commonly associated with hematologic malignancies. Our case illustrates a rare example of fatal tumor lysis syndrome in the setting of metastatic gastric adenocarcinoma treated with radiation therapy. This case highlights the critical importance of identifying patients with solid organ malignancies at risk for tumor lysis syndrome and of early recognition and treatment of this syndrome.